2008
DOI: 10.3198/jpr2007.11.0601crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of TIL:455, TIL:514, and TIL:642, Three Rice Germplasm Lines Containing Introgressed Sheath Blight Resistance Alleles

Abstract: Three rice (Oryza sativa L.) germplasm lines designated as TIL:455 (Reg. No. GP‐112, PI 642943), TIL:514 (Reg. No. GP‐113, PI 642944), and TIL:642 (Reg. No. GP‐114, PI 642945) contain a total of eight novel alleles with sheath blight (caused by Rhizoctonia solani Kühn) resistance backcrossed into an elite U.S. rice genetic background having good grain quality traits, early maturity, and glabrous leaves and hulls. These three germplasm lines were jointly released in 2007 by the USDA‐ARS, the Louisiana State Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Interestingly, the introgression of QTL‐qSB‐9Tq (Teqing) into nine different japonica cultivars from different ecological regions decreased ShB score by 0.5–1.3 (Zuo et al , ). Notably, three rice lines TIL (Teqing‐into‐Lemont backcross introgression lines): 455, TIL:514 and TIL:642 containing 8 introgressed ShB resistance alleles have been released jointly by the USDA‐ARS, the International Rice Research Institute and the Louisiana State University Agricultural Center in 2007 (Pinson et al , ). These TIL lines showed significantly improved ShB resistance in 4 of the 5 year‐location combinations.…”
Section: Quantitative Trait Loci (Qtl)‐based Resistancementioning
confidence: 99%
“…Interestingly, the introgression of QTL‐qSB‐9Tq (Teqing) into nine different japonica cultivars from different ecological regions decreased ShB score by 0.5–1.3 (Zuo et al , ). Notably, three rice lines TIL (Teqing‐into‐Lemont backcross introgression lines): 455, TIL:514 and TIL:642 containing 8 introgressed ShB resistance alleles have been released jointly by the USDA‐ARS, the International Rice Research Institute and the Louisiana State University Agricultural Center in 2007 (Pinson et al , ). These TIL lines showed significantly improved ShB resistance in 4 of the 5 year‐location combinations.…”
Section: Quantitative Trait Loci (Qtl)‐based Resistancementioning
confidence: 99%
“…Zuo et al (2008) demonstrated the potential of qSB-9 TQ in molecular breeding of japonica rice for ShB resistance although the resistance level of Teqing was lower than that of the japonica cultivars. Similarly, Pinson et al (2008), using the markers tightly linked to ShB-QTL, performed marker-assisted selection to introgress resistant alleles from Teqing (PI 536047) into three rice germplasm lines that have been released as varieties in the USA.…”
Section: Qtl Validation and Use In Marker-assisted Selectionmentioning
confidence: 99%
“…The population of TILs contains 123 unique combinations of molecularly tagged genomic segments from TeQing now introgressed into a genetic background selected to be ≥65% from Lemont, based on data from 178 simple sequence repeat (SSR) markers (Pinson et al, 2012). This allows the TILs to serve not just as a mapping population (Pinson et al, 2012, 2015; Wang et al, 2012; Zhang et al, 2014) but also as a source of breeding parents useful for introducing targeted molecularly tagged indica alleles into tropical japonica breeding programs (Pinson et al, 2008). By isolating specific genomic regions from TeQing in a predominantly Lemont genetic background, the TILs allow researchers to measure the genetic effect (i.e., agronomic value) of the indica alleles after their introgression into a tropical japonica genetic background adapted to commercial production in the southern United States.…”
Section: Methodsmentioning
confidence: 99%
“…The two predominant international market classes for rice are (i) long‐grain length with intermediate amylose content (19–23%) and intermediate gelatinization temperature, and (ii) medium grain length with low amylose content (12–19%) and low gelatinization temperature (USA Rice Federation, 2014). TeQing produces grains with an atypical combination of medium grain length, high (≥23%) amylose content, and intermediate gelatinization temperature (Pinson et al, 2008).…”
Section: Molecular Marker Characterizations Associated With Quantitatmentioning
confidence: 99%